Role of Rho-associated kinases and their inhibitor fasudil in neurodegenerative diseases - Ye, Qiuyan; Li, Xue; Gao, Wei; Gao, Jiayue; Zheng, Liping; Zhang, Miaomiao; Yang, Fengge; Li, Honglin (Frontiers in Neuroscience, 2024)
Neurodegenerative diseases (NDDs) are prevalent in the elderly. The pathogenesis of NDDs is complex, and currently, there is no cure available. With the increase in aging population, over 20 million people are affected by common NDDs alone (Alzheimer’s disease and Parkinson’s disease). Therefore, NDDs have profound negative impacts on patients, their families, and society, making them a major global health concern. Rho-associated kinases (ROCKs) belong to the serine/threonine protein kinases family, which modulate diverse cellular processes (e.g., apoptosis). ROCKs may elevate the risk of various NDDs (including Huntington’s disease, Parkinson’s disease, and Alzheimer’s disease) by disrupting synaptic plasticity and promoting inflammatory responses. Therefore, ROCK inhibitors have been regarded as ideal therapies for NDDs in recent years. Fasudil, one of the classic ROCK inhibitor, is a potential drug for treating NDDs, as it repairs nerve damage and promotes axonal regeneration. Thus, the current review summarizes the relationship between ROCKs and NDDs and the mechanism by which fasudil inhibits ROCKs to provide new ideas for the treatment of NDDs.